2014
DOI: 10.3390/ma7064555
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Printed Circuit Boards for Metal and Energy Recovery after Milling and Mechanical Separation

Abstract: The proper disposal of electrical and electronic waste is currently a concern of researchers and environmental managers not only because of the large volume of such waste generated, but also because of the heavy metals and toxic substances it contains. This study analyzed printed circuit boards (PCBs) from discarded computers to determine their metal content and characterized them as solid waste and fuel. The analysis showed that PCBs consist of approximately 26% metal, made up mainly of copper, lead, aluminum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(80 citation statements)
references
References 26 publications
1
71
1
7
Order By: Relevance
“…Kumar et al showed that the concentration of copper, silver, gold, and palladium in e-waste is 5 to 250% higher than average mining operations which provide major economic benefits for recycling [11]. The average metal content in PCBs is approximately 30-35% and rest of the material is referred to as non-metal [12][13][14]. The metals in PCBs are extracted for their value and the remaining nonmetal fraction (NMF) containing the The recovery of metals from the waste printed circuit boards can be achieved by physical or chemical processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al showed that the concentration of copper, silver, gold, and palladium in e-waste is 5 to 250% higher than average mining operations which provide major economic benefits for recycling [11]. The average metal content in PCBs is approximately 30-35% and rest of the material is referred to as non-metal [12][13][14]. The metals in PCBs are extracted for their value and the remaining nonmetal fraction (NMF) containing the The recovery of metals from the waste printed circuit boards can be achieved by physical or chemical processing.…”
Section: Introductionmentioning
confidence: 99%
“…Ning et al summarized that jigging can achieve a high metal recovery of up to 97%, whereas air classification can remove 97% of copper in the sink [22]. Using heavy liquid of density 2.89 g/cm 3 , Bizzo et al separated the NMF from the PCB and thus increased the calorific value to 11.63 GJ/t in the NMF [12]. Chemical recycling based on pyro, hydro and bio-metallurgy has also been utilized for metal recovery [21][22][23]24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Practically all electronic devices contain printed circuit boards (PCBs), which can be considered raw material for metal recovery [3]. The biggest problem associated with PCB recycling is related to its complex structure and material composition.…”
Section: Introductionmentioning
confidence: 99%
“…Using heavy liquids of the specific gravity of 2.89, the metal fraction was separated and the calorific value of the nonmetal fraction was estimated to be 11.63 GJ/t [7]. Researchers have shown the application of gravity separation and flotation to separate metals from nonmetals with high efficiency [5,8,9].…”
Section: Introductionmentioning
confidence: 99%